Intergenerational Occupational Mobility in Colombia: An Intersectional Approach - Viáfara-López, Carlos Augusto (Sociedad y Economía, 2023)
This paper assesses the effect of social class of origin, skin color and gender on intergenerational occupational mobility in Colombia. A descriptive analysis of mobility tables was used, and log-linear models were applied to the latter. The results reveal that, in general, darker skin colors are associated with lower absolute mobility rates. However, in relative mobility, the pattern of association between origins and destinations is similar, although with greater inequality of opportunities for people with darker skin colors. Inequalities according to skin color are greater among women than among men.